Semifield Evaluation of Improved Passive Outdoor Host Seeking Device (POHD) for Outdoor Control of Anopheles arabiensis Mosquitoes - Stella T. Kessy; Bruno A. Nyundo; Ladslaus L. Mnyone; Issa N. Lyimo (The Scientific World Journal)
Despite the considerable progress made so far, the effectiveness and mass application of odour-baited outdoor mosquito control devices in pipelines is limited by several factors. These include the design and size of the devices, optimal placement of attractive blends, and nature of materials into which the blends are impregnated. The primary aim of this study was to manipulate these factors to improve the attractiveness of our recently developed passive outdoor host seeking device (POHD) to outdoor biting Anopheles arabiensis. Specifically, the study aimed to determine optimal placement of odour blends and killing bioactives in POHD for maximum attraction and killing of An. arabiensis and to assess the effects of blend types, formulation, and residual activity on attractiveness of the POHD to An. arabiensis. The POHDs baited with attractive blends, carbon dioxide (CO2), and bendiocarb-treated electrostatic netting were placed either towards the top or bottom openings, and other modifications were exposed to An. arabiensis under the semifield system at Ifakara Health Institute (IHI). Each night, a total of 100 starved female, 3–7-day-old, semifield reared An. arabiensis mosquitoes were released, collected the next morning (alive or dead), counted, and recorded. Live mosquitoes were maintained in the semifield insectary and monitored for 24 hours mortality. Each treatment combination of the POHD was tested in three replicates. Overall, the results indicated that the proportion of mosquitoes attracted to and killed in the POHD varied with position of attractants and killing agent (bendiocarb). The POHD with bottom placed attractants and bendiocarb attracted and killed higher proportion of mosquitoes compared to the POHD with top placed attractants and bendiocarb. The highest mortalities were observed when the POHD was baited with a combination of attractive blends and CO2. Moreover, the residual activity of attractive blends applied inside POHD varied with type and formulation of attractive blend. The POHD packed with Mbita and Ifakara blend in microencapsulated pellets (granules) attracted higher proportion of mosquitoes than that baited with soaked nylon-strip formulation of either blends. Interestingly, POHD baited with Mbita blend in microencapsulated pellets (granules) formulation attracted and killed higher proportion of mosquitoes (>90%) than that baited with Ifakara blend even 9 months after application. Conclusively, the POHD remained effective for a relatively longer period of time when baited with bottom placed synthetic blends and CO2 combination, thus warranting further trials under real life situations.